Pengaruh Kecerdasan Emosional, Kecerdasan Spiritual, dan Locus of Control terhadap Kecenderungan Kecurangan Akuntansi - Gian Javier Fausta; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2022)
The purpose of this study was to examine the effect of emotional intelligence, spiritual intelligence, and locus of control on the tendency of accounting fraud. The population in this study is the regional work unit in Tanah Datar Regency, totaling 24 SKPD, and the respondents are the head of the office, the head of the finance department, and staff from each SKPD. The research design used in this study is a quantitative approach using primary data. Primary data was obtained by distributing questionnaires directly to 72 respondents. The data was then analyzed using multiple linear regression techniques. The results of this study are (1) emotional intelligence has no effect on the tendency of accounting fraud in the Regional Work Unit (SKPD) of Tanah Datar Regency, (2) spiritual intelligence has a negative and significant effect on the tendency of accounting fraud in the regional work unit (SKPD) of Tanah Datar Regency. (3) Internal locus of control has no effect on the tendency of accounting fraud in the regional work unit (SKPD) of Tanah Datar Regency.